Protecting the rights of old people in Nigeria: towards a legal reform (2015)
There are certain rights that are fundamental and should be enjoyed by everybody regardless of gender, tribe, colour, creed and age. The society sees some people as vulnerable and as such will require its protection. A category of such vulnerable in the society is the old people that need special attention because of their weak nature and low production capacity. The nature of the old people has no doubt captured the attention of the international community who offers some legal protections to them by the provisions of various treaties and conventions. The aim of this article is to consider the legislation, if any, and policy development in the care of old people in Nigeria. It therefore germane to review what the law offers to protect this category of people in Nigeria in comparison with the standard required at the international scene.